Hijab in the Public Sphere of Muslim Countries in Southeast Asia, Media, State Rules, and Society Opinion - Sonezza Ladyanna (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2024)
This article aims to explain state regulations and media perspectives in Muslim-majority countries in Southeast Asia regarding the use of the hijab as a religious symbol in public spaces. The influence of globalization has increased diversity in the media landscape in the public sphere, going beyond traditional face-to-face interactions and encompassing the vast realm of the Internet. While Muslim women in secular Western countries face bans on wearing the hijab in public spaces, Muslim women in Muslim-majority countries in Southeast Asia face challenges regarding their style of wearing the hijab in public spaces. This research is qualitative research based on the study of public space and religion. The analysis was carried out in three Southeast Asian countries, namely Indonesia, Malaysia, and Brunei Darussalam, which have Muslim populations with different characteristics. Indonesia and Malaysia are multicultural regions but are dominated by Muslims, and Brunei is a country with a Muslim majority. These three countries have different patterns of managing religion in public spaces. Religious symbols in public spaces reflect the relationship between public space phenomena, the state, and the social context in a region. Social media has expanded the public sphere, providing greater opportunities for religious groups to present their arguments or engage in da'wah (religious outreach).